Student assessment and learning guide : - Nickels, William G. (McGraw-Hill/Irwin, 2005)
This study guide contains various forms of open-ended questions that require the student to write out his or her personal summary of the material. The guide gives students the opportunity not only to prepare for tests but also to develop and practice their business knowledge and skills. The following materials are provided for every chapter: learning goals, chapter outline, key terms and definitions, retention questions, critical thinking questions, Internet exercises, and a practice test. As always, this student guide was reviewed for format and accuracy before being printed.